The Impact Board Attributes On ESG Disclosure - Warsito; Rizka Putri Pebrianti; Adella Hafshah Sya’rani; Erezha Rezhilena Sitepu (Hikamatzu | Journal of Multidisciplinary, 2026)
corporate behavior and ensuring business sustainability in relation to their investment decisions. This study aims to examine the board attributes that influence ESG disclosure. The board attributes analyzed include board size, gender diversity, and board independence. The research focuses on food and beverage subsector companies listed on the Indonesia Stock Exchange during the period 2021–2023. Hypothesis testing was conducted using a multiple linear regression model. Results indicate that board attributes, board size have a positive and significant relationship with ESG disclosure. However, no significant association is found between gender diversity, board independence and ESG disclosure. In line with stakeholder theory, the disclosure of ESG information to all stakeholders is an important factor in creating the company’s competitive advantage